Association between the Systemic Immune-Inflammation Index and Thyroid Function in U.S. Adults - Xin-Yu Hu; Ying-Chao Liang; Huan-Huan Zhang; Hui-Lin Li; De-Liang Liu (Mediators of Inflammation)
Background. The systemic immune-inflammation index (SII) is used as an indicator of prognosis for a wide range of diseases. Thyroid function has been found to be strongly associated with inflammation. The purpose of this investigation was to analyze the correlation between SII and various thyroid functions. Methods. This study utilized data from the National Health and Nutrition Examination Survey (NHANES) 2007–2012. The association between SII and thyroid function was analyzed using weighted univariate and multivariate linear regression analyses. Subgroup analyses, interaction tests, and weighted restricted cubic spline (RCS) regression analyses were also employed to test this correlation. Results. Of the 6,875 participants (age ≥ 20 years), the mean age was 46.87 ± 0.40 years. The adjusted model showed that lnSII was negatively correlated with FT3 (β = −0.0559, 95% CI −0.1060 to −0.0059,) and FT3/FT4 (β = −0.0920, 95% CI −0.1667 to −0.0173,). There was a positive correlation between lnSII and TT4 (β = 0.1499, 95% CI 0.0722–0.2276,). In subgroup analyses, lnSII still independently affected a wide range of thyroid functions. Weighted RCS analysis showed a nonlinear relationship between FT3 and lnSII. Conclusion. Close relationships exist between SII and a variety of thyroid functions. SII can be used as an indicator to predict thyroid dysfunction. Control of inflammatory activity may be a protective measure against thyroid dysfunction. More large-scale prospective studies are necessary to further explore the correlation between SII and thyroid function and the role of obesity in this.